Experiences of Mental Healthcare Reported by Individuals Diagnosed with Bipolar Disorder: An Italian Qualitative Study - Vallarino, Martine; Rapisarda, Filippo; Scott, Jan; Vecchi, Tomaso; Barbato, Angelo; D’Avanzo, Barbara (Community mental health journal, 2019)
This qualitative study explores experiences of mental health care by nine Italian users with a diagnosis of bipolar disorder. The findings from semi-structured interviews carried by professional researchers highlighted the following themes: mixed feelings about the diagnosis; lack of access to psychological interventions despite preferences of users; positive view of peer support, job as a safe haven, traumatic experiences of compulsory hospital admissions; need for crisis interventions as alternative to hospital admission. Most users’ views look in accordance with evidence-based recommendations seldom implemented in practice. Future research directions, implications of users’ expectations and experiences for service planning and quality improvement, are presented and discussed in the light of the qualitative available literature.